The impact of human capital development on the economic and social development of a country: empirical study (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Methodologically this research is based on the approach of many social scientists who argue that there is a bidirectional link: one runs from human capital development to economic growth and overall human development, when human capital helps increase national income and society development; the other runs from economic growth to human capital development, as the resources from national income are allocated to activities contributing to human capital development. The study aims to empirically verify the existence of this interaction by carrying out a correlation analysis of the human capital development level among 120 countries, assessed by the Human Capital Index, and the world's national economic development level, as demonstrated by the Global Competitiveness Index, as well as the level of development of the world's nations (societies) as demonstrated by the Human Development Index.The result of the analysis empirically demonstrated a strong link between the human capital development with the country's economic (r = +0.944, p = 0.000) and national development (r = +0.882, p = 0.000) in total by all countries. Nevertheless, carrying out the correlation analysis by groups of countries, which are divided according to the calculation methodology of the Global Competitiveness Index, depending on their stage of economic development, the relationship between human capital development and nation’s development is becoming weaker in some groups of countries, with the remaining strong correlation between the development of human capital and the economic development of a state in all groups of countries. This means that only highly developed human capital can contribute to the country's economic development, and vice versa, national economic performance increases human capital development in the framework of effective development policy. On the other hand, not always a close interaction between nation’s development and human capital development can be faced, since a highly developed human capital means the quality of the developed human capital